A Statewide Study of Gang Membership in California Secondary Schools. (September 2016) - Estrada, Joey Nuñez; Gilreath, Tamika D.; Astor, Ron Avi; Benbenishty, Rami
To date, there is a paucity of empirical evidence that examines gang membership in schools. Using statewide data of 7th-, 9th-, and 11th-grade students from California, this study focuses on the prevalence of gang membership by county, region, ethnicity, and grade level. Bivariate and multivariate logistic regression analyses were employed with gang membership as the outcome of interest. Approximately 8.4% of the student sample reported that they consider themselves to be a member of a gang. Regional-level rates of gang membership across six geographical areas are all in a relatively narrow range and gang members are fairly evenly distributed across California schools. The findings imply that schools are a good place to focus on gang prevention and intervention, and educators need to be aware of the possible gang activity in their schools to provide the appropriate resources, programs, and support for these students.